Integrated Analysis of the Transcriptome and Metabolome Reveals the Network Regulating Fruit Taste in Sponge Gourd (Luffa cylindrica) - Yaqian Chai; Wenjing Qiu; Zhikun Li; Luyao Gao; Wenqi Dong; Peng Zhang; Shengjun Zhou; Xin Wang; Yuqiang Zhu; Yuyan Sun (Foods)
Sponge gourd fruit is highly favored by consumers because of its nutritional and medicinal properties. Continuous increases in living standards have led to an increase in the demand for high-quality fruits and vegetables. Hence, we explored the mechanisms that regulate fruit taste development. Specifically, two sponge gourd materials, ZS203 (GT) and ZAAS-106 (BT), which differ in fruit taste, were selected for transcriptomic and metabolomic analyses. Ascorbic acid, soluble solids, and crude protein contents were significantly higher in GT than in BT. Similarly, the lysine, phenylalanine, and tryptophan contents were higher in GT than in BT (1.48-, 1.60-, and 1.38 times higher, respectively). Transcriptomic analysis of GT and BT fruits identified 1821 upregulated and 1185 downregulated differentially expressed genes (DEGs) in GT, while metabolomic analysis detected 25 upregulated differentially accumulated metabolites (DAMs) and 28 downregulated DAMs in GT. A correlation analysis suggested that DAMs and DEGs related to vitamin B6 metabolism, tryptophan metabolism, and phenylalanine metabolism contribute to the differences in sponge gourd fruit taste; a potential mechanism underlying this diversity was proposed. Additionally, expression data for the 15 DEGs were consistent between transcriptomic and qRT-PCR analyses. Notably, this study revealed a potential mechanism for regulating differences in sponge gourd fruit taste, with possible implications for breeding novel varieties with optimized fruit taste.